THE EFFECT OF THE PROJECT BASED LEARNING MODEL ON THE LEARNING OUTCOMES OF HIGH SCHOOL STUDENTS IN PASCAL'S LEGAL MATERIAL - Fajar Gohanda Sinaga; Mula Sigiro; Josafat Alexander, Irving (Jurnal Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the influence of the Project-Based Learning (PjBL) model on the learning outcomes of high school students in Pascal's Law material. The background of this research is the low level of students' understanding of Pascal's Law, which is often taught theoretically, so it is less contextual and can be applied. This study uses a quantitative approach with quasi-experimental methods and Pretest-Posttest Design of Control Groups. The research subjects were 11th grade students of SMA Negeri 1 Sei Bamban for the 2024/2025 academic year, with a total sample of 60 students, consisting of 30 students in the experimental class and 30 students in the control class, selected using purposive sampling. The research instrument consisted of a multiple-choice learning outcome test with 20 validated items and an observation sheet of student activities. The results showed that the average pretest scores of the two classes were relatively equivalent (experimental = 45.33; control = 45.17) with a significance value of 0.960 (>0.05), indicating no significant difference in initial ability. After treatment, the average post-experimental class score increased to 78.67, while the control class only reached 66.33. The t-test reveals a significant difference between the two classes (Sig. <0.05). Student activity in the experimental class was also recorded high, with an average of 79.97% in the active category. It can be concluded that the application of the Project-Based Learning model has a significant influence on improving student learning outcomes in Pascal's Law compared to conventional learning. These findings reinforce previous literature on the effectiveness of PjBL as an innovative learning strategy that is able to connect abstract concepts with students' real-life experiences.